Local Photovoltaic Properties of Graphene–Silicon Heterojunctions. Issue 12 (21st September 2018) - Rahova, Jaroslava; Sampathkumar, Krishna; Vetushka, Aliaksei; Ledinsky, Martin; Hajkova, Zdenka; Fejfar, Antonin; Frank, Otakar
Abstract : Interfacing of materials with different dimensionalities becomes increasingly relevant for many applications which can utilize the exceptional properties of low‐dimensional materials on one hand, and build‐up on the existing production know‐how for bulk (3D) materials on the other. Numerous appealing possibilities are offered by such combinations. In this work, the authors focus on 2D–3D heterostructures composed of mechanically exfoliated single‐ and few‐layer layer graphene (Gr) coupled to freshly etched n‐doped silicon. Two ways of characterizing the photovoltaic (PV) properties of such junctions by Conductive Atomic Force Miscroscopy (C‐AFM) under illumination are shown: 1) by measuring the I–V curves directly at selected points, while the flakes are scanned in intermittent mode and 2) by scanning the samples in contact mode at different bias voltages, followed by reconstruction of I–V curves using mean photocurrent quantified in selected areas. The direct I–V curves measurement has been employed to discriminate the effect of increased p‐doping of the graphene layer, and the contact mode has been utilized to evaluate the separation between the graphene flake and the substrate. Additionally, pros and cons of the two routes are briefly discussed and outlook for further advanced nanoscale characterization of such junctions is proposed. Abstract : Local photovoltaic properties of graphene–silicon Schottky junction can be quantified by atomic force microscopy (AFM)‐based techniques. Point measurement or reconstruction of I–V curves from scanning in contact mode can be used, employing even only the red AFM diode. As examples, the negligible influence of the graphene layer number on the photovoltaic properties, the increased work function by AuCl3 doping, and the effect of graphene–silicon separation are documented.